Essays on subjective wellbeing and behaviour - Overdick, K (2023)
This thesis seeks to improve our understanding of the relationship between behaviour and subjective wellbeing (SWB). The thesis looks at three different sides of this relationship in the three main chapters. First, I conduct experiments to analyse the effect of happiness on willingness to compete (WTC). Happiness does not change WTC significantly. Subjective attitudes toward competition are mediators for WTC and provide a potential explanation for this null result. Second, the thesis analyses the relationship between SWB and a set of behavioural preferences in a global data set. SWB is usually positively correlated to the preferences meaning that for example being more patient or risk-taking is correlated with higher SWB. The coefficients are remarkably similar for the different regions of the world. Third, the thesis estimates the effect of mass shootings as a form of extreme behaviour on SWB. The results show that the effect of mass shootings on life satisfaction is relatively small and short-lived.